The isomer-sensitive electrochemical HER of ruthenium(II)-hydrido complexes involving redox-Active azoheteroaromatics - Seikh L.; Dhara S.; Singh A.K.; Singh A.; Dey S.; Indra A.; Lahiri G.K. (My University, 2025)
The article deals with the development of isomeric ruthenium(II)-hydrido complexes [RuII(H)(L1) (PPh3)2(CO)]ClO4 ([1a]ClO4-[1b]ClO4)/[RuII(H)(L2)(PPh3)2(CO)]ClO4 ([2a]ClO4-[2b]ClO4) involving azo coupled L1 [L1: (E)-1,2-bis(1-methyl-1H-pyrazol-3-yl)diazene]/L2 [L2: (E)-1,2-bis(4-iodo-1-methyl-1Hpyrazol-3-yl)diazene], respectively. Structural evaluation of the complexes affirmed the syn conformation of the coordinated/uncoordinated pyrazole groups of L and its unperturbed neutral azo (NvN) state. Isomeric forms in [1a]ClO4/[1b]ClO4 or [2a]ClO4/[2b]ClO4 differed with respect to the cis and trans orientations of the coordinated CO and N(azo) donor of L, respectively. It also demonstrated the formation of intermolecular hydrogen-bonded dimeric or 1D-polymeric chains in [1a]ClO4/[2b]ClO4 or [1b]ClO4, respectively. Successive two-electron reductions of the complexes varied to an appreciable extent as a function of the heterocycles connected to L. The involvement of the azo function of L towards the reductions ([NvN]0 [NvN] [NvN]2-) was supported by the DFT calculated MOs and Mulliken spin density at the paramagnetic state, which was further validated by the radical EPR profile of the first reduced (S = 1/2) state. Isomeric [1a]ClO4/[1b]ClO4 or [2a]ClO4/[2b]ClO4 immobilised on the carbon cloth support underwent various electrochemical acidic HERs (hydrogen evolution reactions) with TOF/ 10-1 s-1: [1a]ClO4 (0.83) [1b]ClO4 (0.68) [2a]ClO4 (0.50) [2b]ClO4 (0.37). © 2023 Royal Society of Chemistry. All rights reserved.